Therapeutic Applications of Cell Microencapsulation - Pedraz, Jose Luis.; Orive, Gorka; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The advancement of science is ever more contingent upon the interaction of experts vast amount of scientific information being gathered every day that exceeds the ability of any one scientist to acquire. As an illustration of the frantic pace of scientific disc- more acute in the case of scientific fields at the interface of different and seemingly distant areas of study. Amidst these, the field of cell encapsulation brings together an array of diverse disciplines such as molecular biology and biopolymers, gene therapy and inorganic membranes, stem cell biology and physicochemistry, immunology and nanotechnology. Clearly, such range of topics is too broad for any individual scientist the state-of-the-art in the field of cell encapsulation. At the core of this technology, there is an interaction of physicochemical and biological elements forming three distinct layers of complexity. First, the chemistry of the biopolymer dictates the degree of protein adsorption, vascularization, tox- ity and biocompatibility of the microcapsules. Advances in biopolymer science are providing solutions to overcome existing challenges and to improve microcapsules as delivery vehicles. Second, the choice of cells, and more precisely the plethora of in determining the immune response elicited by the host to implanted microcapsules.
Highlights and Trends in Cell Encapsulation -- Biomaterials in Cell Microencapsulation -- Development of Subsieve-Size Capsules and Application to Cell Therapy -- Regulatory Considerations in Application of Encapsulated Cell Therapies -- Treatment of Diabetes with Encapsulated Islets -- Epo Delivery by Genetically Engineered C2C12 Myoblasts Immobilized in Microcapsules -- Artificial cell microencapsulated stem cells in regenerative medicine, tissue engineering and cell therapy -- Microencapsulated Choroid Plexus Epithelial Cell Transplants for Repair of the Brain -- Therapeutic Application of Cell Microencapsulation in Cancer -- Inorganic Nanoporous Membranes for Immunoisolated Cell-Based Drug Delivery -- Cell Microencapsulation -- Commercial Applicability of Cell Microancapsulation: A Review of Intellectual Property Rights.
Keywords: Medicine; Medical microbiology; Biomedicine, general; Medical Microbiology